A prosodic constraint on wh-extraction from preverbal infinitival subjects - Muñoz Pérez, Carlos (2022)
This paper introduces a series of mitigating circumstances improving the acceptability of wh-extraction from preverbal infinitival subjects in Rioplatense Spanish. It is argued that the factor behind these amelioration effects is encoded in prosodic structure, much in line with the hypothesis that certain island restrictions apply at PF. The linguistic principle accounting for the phenomenon is proposed to be a faithfulness constraint at the syntaxprosody interface stating that an extraction domain XP cannot be mapped as a prosodic word ω at PF. An alternative syntactic account based on freezing is shown to be unable to capture the relevant contrasts.